Pentanol/diesel fuel blends: Assessment of inhalation cancer risk and ozone formation potential from carbonyl emissions emitted by an automotive diesel engine. (1st August 2022) - Arias, Silvana; Botero, Maria L.; Molina, Francisco; Agudelo, John R.
Graphical abstract: Highlights: Carbonyl emissions were assessed with pentanol/diesel blends under two representative modes of urban driving conditions. Pentanol increase carbonyl specific emissions of the gas phase. Carbonyl specific emissions decrease with increasing engine load. Pentanol increased ozone formation potential and inhalation cancer risk for a trespasser/recreational receptor. Abstract: Pentanol has recently drawn particular attention as a fuel for diesel engines due to its higher energy density and its renewable nature. However, it is well known that oxygenated fuels increase carbonyl emissions, that are harmful to human health. In this study, carbonyl compounds emitted by an automotive diesel engine fueled with pentanol and ultra-low sulfur diesel (ULSD) blends were investigated. Three ULSD-pentanol blends were studied: 13%, 15.5% and 20% by volume. A common-rail, direct-injection diesel engine equipped with exhaust gas recirculation system and diesel oxidation catalyst was operated under two representative urban driving modes (M1: 1750 rpm and 71Nm; M2: 2450 rpm and 90Nm). Carbonyls were sampled from the undiluted exhaust by trapping the gas with 2, 4-DNPH cartridges and analyzed by HPLC-UV. The impact of carbonyl specific emissions on the ozone formation potential (OFP in mg O3 /kWh) was determined and their estimated inhalation cancer risk (CR) associated with carcinogenic compounds such as formaldehyde and acetaldehyde were quantified. Results indicate that total specific carbonyl emissions increased significantly with pentanol addition, and a maximum was observed with the 15% blend for both engine operating modes. The emissions of all measured carbonyls decreased for the high engine load. Formaldehyde, acetaldehyde, acetone and acrolein were the most abundant carbonyls independently of the fuel tested. The OFP increased with pentanol blends by up to a factor of 2 for M1 and 4 for M2. The estimated inhalation CR increased up to 5x with pentanol blends for a specific exposure scenario evaluated. According to the results obtained in this work, the CR are below the threshold suggested U.S EPA, however, the CR were calculated considering two relevant aldehyde compounds. To reach a representative cancer risk assessment, the greatest possible quantity of carcinogenic volatile organic compounds (VOCs) should be measured.